Descemet Membrane Endothelial Keratoplasty After Penetrating Keratoplasty: Features for Success. Issue 9 (September 2018) - Einan-Lifshitz, Adi; Belkin, Avner; Sorkin, Nir; Mednick, Zale; Boutin, Tanguy; Gill, Ishrat; Karimi, Mohammad; Chan, Clara C.; Rootman, David S.
Abstract : Purpose: To evaluate Descemet membrane endothelial keratoplasty (DMEK) in the setting of failed penetrating keratoplasty (PKP) and to identify factors associated with DMEK success and failure after PKP. Methods: A retrospective chart review of patients who underwent DMEK for failed PKP at Toronto Western Hospital, Canada, between 2014 and 2017 was performed. Demographic characteristics, number of previous transplants, intraoperative and postoperative complications, best spectacle-corrected visual acuity (BSCVA), and endothelial cell density were analyzed. Results: Twenty-eight eyes were included in the study. Rebubbling intervention was performed in 12 eyes (43%) within the first postoperative weeks. Five eyes (18%) developed graft rejection episodes. Twelve eyes (43%) had to be regrafted after DMEK surgery and were deemed failures (because of persistent Descemet membrane detachment, rejection episode that led to secondary failure, and infection). BSCVA before DMEK was significantly worse in the eyes that failed than those that did not [1.97 ± 0.85 and 1.2 ± 0.56 logMAR, respectively, ( P = 0.01)]. Rebubbling was required in 75% of eyes in the failure group compared with 19% in the success group ( P = 0.002). Six of the 16 eyes (37.5%) in the success group underwent femtosecond laser-enabled DMEK, whereas this technique was not used in any of the eyes in the failure group ( P = 0.017). Conclusions: DMEK is a viable option for cases of failed PKP. DMEK failure after PKP might be associated with lower visual acuity before DMEK surgery, higher number of rebubble interventions, and manual descemetorhexis rather than femtosecond laser-enabled DMEK.